Pengaruh Influencer Marketing, Brand Trust, dan Harga terhadap Minat Beli Produk Skintific - Tria Nurul Arofah; Mochammad Isa Anshori (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the extent of the influence of influencer marketing, brand trust, and price on buying interest in Skintific products for students of the Faculty of Economics and Business, Trunojoyo University Madura. This study uses a quantitative approach with a population of students who have watched the promotional content of Skintific products by influencers and have interest and experience in using these products. A total of 100 respondents were selected using purposive sampling method. Data was collected through distributing questionnaires and analyzed using multiple linear regression techniques. The research findings indicate that influencer marketing does not have a significant influence on purchase intention. In contrast, brand trust and price variables show a positive and significant influence on purchase intention of Skintific products.